2015
DOI: 10.4236/ijcm.2015.610101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Risk Factor in Patients with STEMI Treated with Percutaneous Coronary Intervention

Abstract: This study was carried out to analyze risk factors and short-term clinical outcomes in different age groups of Indian patients with ST-elevation myocardial infarction who underwent percutaneous coronary intervention. This prospective, non-randomized, and observational study was carried out at a tertiary care hospital. The patients who were treated with primary percutaneous coronary intervention for ST-elevation myocardial infarction at study center from December 2011 to September 2012 were included in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Although our sample size is not very large, it is still among the largest reports of STEMI in young patients in the Middle East. And, unlike other published reports of myocardial infarction in young adults in developing countries,[ 11 12 36 ] our study was a multicenter study that followed patients prospectively for one year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although our sample size is not very large, it is still among the largest reports of STEMI in young patients in the Middle East. And, unlike other published reports of myocardial infarction in young adults in developing countries,[ 11 12 36 ] our study was a multicenter study that followed patients prospectively for one year.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with other reports from developing countries where 80% of the young (≤40) STEMI patients from Kannur, India and 62% of the young (<40 years) STEMI patients from Abu Dhabi, UAE had single-vessel disease. [ 5 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Several studies have reported a 1-16% prevalence of AMI in young populations. [1][2][3][4][5][6][7][8] Several causes and risk factors for premature MI have been highlighted, including mental stress, excessive workload, smoking, sedentary lifestyle, unhealthy dietary habits, and addiction. 2,6 Although AMI in young individuals has a relatively better prognosis, [9][10][11] its social and economic burden is critical for both family and society during the productive years of life.…”
Section: Introductionmentioning
confidence: 99%